Auditory Perception of a Human Walker. (November 2014) - Cottrell, David; Campbell, Megan E J
When one hears footsteps in the hall, one is able to instantly recognise it as a person: this is an everyday example of auditory biological motion perception. Despite the familiarity of this experience, research into this phenomenon is in its infancy compared with visual biological motion perception. Here, two experiments explored sensitivity to, and recognition of, auditory stimuli of biological and nonbiological origin. We hypothesised that the cadence of a walker gives rise to a temporal pattern of impact sounds that facilitates the recognition of human motion from auditory stimuli alone. First a series of detection tasks compared sensitivity with three carefully matched impact sounds: footsteps, a ball bouncing, and drumbeats. Unexpectedly, participants were no more sensitive to footsteps than to impact sounds of nonbiological origin. In the second experiment participants made discriminations between pairs of the same stimuli, in a series of recognition tasks in which the temporal pattern of impact sounds was manipulated to be either that of a walker or the pattern more typical of the source event (a ball bouncing or a drumbeat). Under these conditions, there was evidence that both temporal and nontemporal cues were important in recognising theses stimuli. It is proposed that the interval between footsteps, which reflects a walker's cadence, is a cue for the recognition of the sounds of a human walking.